2021
DOI: 10.3390/molecules26123558
|View full text |Cite
|
Sign up to set email alerts
|

From Prebiotic Chemistry to Supramolecular Biomedical Materials: Exploring the Properties of Self-Assembling Nucleobase-Containing Peptides

Abstract: Peptides and their synthetic analogs are a class of molecules with enormous relevance as therapeutics for their ability to interact with biomacromolecules like nucleic acids and proteins, potentially interfering with biological pathways often involved in the onset and progression of pathologies of high social impact. Nucleobase-bearing peptides (nucleopeptides) and pseudopeptides (PNAs) offer further interesting possibilities related to their nucleobase-decorated nature for diagnostic and therapeutic applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 129 publications
0
23
0
Order By: Relevance
“…43,44 Thus, thanks to the wealth of possibilities for the modulation of the two constitutive parts, i.e., the peptide (e.g., length, sequence, nature of the amino acids) and the nucleobase-containing (e.g., number, sequence, position in the peptide, nature of the base, type of derivative considered) moieties, nucleopeptides appear as a highly versatile class of molecules with almost virtually infinite possibilities in terms of design and molecular structures, offering to chemists a fascinating field to explore and to understand. 29 While not found in Nature (except for the nucleoamino acid willardiine) and that their prebiotic role has been hypothesized, [45][46][47] nucleopeptides are mainly synthetic compounds developed for biological applications 47 thanks to their ability to interact with proteins or enzymes such as serum albumin 48 or the reverse-transcriptase of HIV. 49 Harnessing the abilities of peptides and nucleobases to self-assemble in specific conditions, several research groups reported on the use of nucleopeptides to study their self-organisation and to develop new properties and applications 29 such as tuneable or functional supramolecular architectures, [50][51][52][53] fluorescence, [54][55][56][57] to selectively sequestrate ATP in cells 58 or to deliver RNA into cells, 59 to name a few.…”
Section: Nucleopeptide Self-assembliesmentioning
confidence: 99%
See 2 more Smart Citations
“…43,44 Thus, thanks to the wealth of possibilities for the modulation of the two constitutive parts, i.e., the peptide (e.g., length, sequence, nature of the amino acids) and the nucleobase-containing (e.g., number, sequence, position in the peptide, nature of the base, type of derivative considered) moieties, nucleopeptides appear as a highly versatile class of molecules with almost virtually infinite possibilities in terms of design and molecular structures, offering to chemists a fascinating field to explore and to understand. 29 While not found in Nature (except for the nucleoamino acid willardiine) and that their prebiotic role has been hypothesized, [45][46][47] nucleopeptides are mainly synthetic compounds developed for biological applications 47 thanks to their ability to interact with proteins or enzymes such as serum albumin 48 or the reverse-transcriptase of HIV. 49 Harnessing the abilities of peptides and nucleobases to self-assemble in specific conditions, several research groups reported on the use of nucleopeptides to study their self-organisation and to develop new properties and applications 29 such as tuneable or functional supramolecular architectures, [50][51][52][53] fluorescence, [54][55][56][57] to selectively sequestrate ATP in cells 58 or to deliver RNA into cells, 59 to name a few.…”
Section: Nucleopeptide Self-assembliesmentioning
confidence: 99%
“…These data highlight the efficiency of low-molecular weight nucleopep-tide-based hydrogels in different experimental conditions, including the formulation, the pH or the nature of the buffer if used, offering several possibilities in terms of applications, from cell culture to long release of anticancer drugs. Nucleopeptides have already been reported for various other applications (vide supra) 29,47,105,106 thanks to their inherent properties derived from their two main constituents, i.e., the peptide and the nucleobase-moiety parts, which can be harnessed for the development of soft materials. While the pros and cons of the former have been discussed hereinbefore (see introduction), 8,14,15,17,18 the latter exhibit different advantages and drawbacks depending on the nature of the derivative.…”
Section: Summary Conclusion and Perspectives Of Low-molecular Weight ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its stacking properties 3′,5′ cGMP can clearly approach a reactive conformation for polymerization on its own and does not need help from any other midwife molecules or activating agents. The ability of biopolymers and their monomers to self-assemble into reactive geometries could play a pivotal role at the emergence of life on our planet [ 30 ].…”
Section: Mechanism Of Ring-opening Polymerization Reactions Involving 3′5′ Cyclic Nucleotidesmentioning
confidence: 99%
“…Surprisingly, many of these critical molecules easily aggregate and accumulate inside living cells through interactions between developed and complex domains. Aggregation may occur incorrectly and lead to disease, but there is growing evidence that the aggregation phenomenon can be regulated by the cell and used to perform important and beneficial biological functions, from molecular scaffolding to memory [6,7]. In industry, proteins are widely used, depending on their specific functional properties.…”
Section: Introductionmentioning
confidence: 99%